Is New Public Management an Option for Post-Pandemic Public Service Delivery in Nigeria? - Wasiu Abiodun Makinde (The Indonesian Institute of Science and Technology Research, 2022)
The expenditure and revenue trajectories which diverge sharply, as well as the increasing demand for better public service in the late 1970s around Western Europe and Northern America, necessitate the introduction of various principles coined as New Public Management (NPM) to reform the longstanding traditional public administration designed along Wilson's politics-administration dichotomy and Weber's ideal model of bureaucracy. With little or no doubt about its effects on the process of public service delivery in advanced nations, much has not been written on the impact on public service delivery in Nigeria and other developing countries amidst challenges impending in the post-pandemic public service delivery in Nigeria. This study evaluates the option of full implementation of new public management for post-pandemic public service delivery in Nigeria. Drawing on theoretical and empirical research, it explores the potential for service quality and cost recovery of public service, decentralization of decision making in public bureaucracies, and whether the process of public service delivery will be enhanced through performance measurement all within the regime of New Public Management. In exploring these issues, this paper sheds light on the potential of New Public Management to stabilize and improve public service delivery in the post-pandemic era of Nigeria.